Pengaruh Penambahan Kerikil Pada Campuran Paving Stone Terhadap Kualitasnya - Suprapto, (Teknika, 2009)
Principal material of paving stone is sand. But sand availability would as component of maker basis paving stone, longer on the wane or increasingly limited. Mining of mass sand, can result area going worse level of the damage. For the purpose must be searched material alternative of lessen, even replaces exploiting of sand as component of building, including also paving stone. Therefore need to be performed a research about paving stone to look for formulation of material mixture and alternative of usage of material besides sand material, and at the same time to increase quality of quality of paving.This research done with making specimen paving with various filler material compositions for mixture, filler besides sand also is added gravel having diameter 4,6 mm and having diameter 5,6 mm . Specimen is made is in the form of box of the size 10 cm x 20 cm x 6 cm. composition of Mixture is made in such a manner, starts from sand filler only, gradual finite of sand is lessened by until without sand. Test quality of paving is done with testing compressive strength and water absorption.Result of research indicates that Gradasi mixture filler paving stone hardly influences strength of the paving, increasingly varies gradation of filler, increasingly good quality of paving Addition of gravel at mixture filler paving stone, can increase the paving compressive strength. improvement of Strength reachs 15,9% for addition of gravel with diameter 4,6 mm and 17,79% for addition of gravel is having diameter 5,6 mm. Addition of gravel having diameter 5,6 mm at mixture filler paving stone has strength of higher compress compared to addition of gravel is having diameter 4,6 mm, the difference can reach 5%. Besides also addition of gravel at mixture paving stone which main filler of sand, also can lessen level of water absorption at the paving.